Intervenciones de enfermería en adultos con artritis reumatoide. - Tingo Ortiz, Belén Sthefannia (2022)
Rheumatoid arthritis (RA) is a systemic autoimmune disease that causes damage to the synovial tissues and is characterized by symmetric polyarticular soreness, which can lead to a progressive joint damage; It is associated with a marked functional disability, increased morbidity, and mortality, which entails an enormous and growing social burden. Statistical data are established, and they indicate that this disease fluctuates between 0.3% and 1% rates at the Ecuadorian territory level, thus highlighting that the average age of diagnosis is between 45 and 64 years of age, highlighting that it can affect both men as women. For this reason, the general objective of the review is to define nursing care in patients with rheumatoid arthritis based on the Kristen M. Swanson theory that allows the identification of diagnoses based on the NANDA, NOC and NIC taxonomy. For this reason, the multidisciplinary team intervention is fundamental, being the nursing role the key for the control of modifiable risk factors; in both, teaching about management, compliance, and adherence to treatment, as well as ways to prevent complications, while patients can obtain information about interventions that promote care and acquire knowledge and skills. It has been established in this research that nursing action is fundamental, especially when healthcare is guiding in some theory, for this reason, Kristen M Swanson is seen as fundamental in this pathology because it involves the patient care through taking shared decisions with the health team, it will improve the function of the patient, by increasing knowledge about the disease, promotes self-efficacy by adding security, continuity and positive feelings, emphasizing that nurses include person-centered care and referral of the activity of the illness.